GEOMETRY TRANSFORMATION MODULE DEVELOPMENT FOR IMPROVE SOLVING ABILITY MATHEMATICS PROBLEMS - Harun Onesimus Laia (Afore : Jurnal Pendidikan Matematika, 2023)
Mathematics is a subject that plays a very important role in various disciplines and can develop human thinking. A math problem is a problem expressed in the form of a question that if someone does not have a rule / law that can be used to solve the question. The purpose of this study were 1) to produce a valid, practical and effective geometry transformation module, 2) to determine the improvement of students' mathematical problem solving ability after using the geometry transformation module. This type of research is research and development (R&D) by developing products in the form of learning modules on geometry transformation material. Data collection techniques are interviews, questionnaires and direct observation. The results of material expert validation obtained an average percentage of 84.7% with very valid criteria, the results of linguist validation obtained an average percentage of 86.1% with very valid criteria, the results of design expert validation obtained an average percentage of 75% with valid criteria and feasible to use. The results of students' responses obtained an average percentage of 85% with very practical criteria, the results of observations of learning activities provided by subject teachers were 100% with very practical criteria. The result of the gain score obtained based on the pretest and posttest of students is 78.4% with the criteria that the developed module is effective. Based on the results of research and discussion in this study, it can be concluded that the development of geometry transformation module to improve mathematical problem solving ability is valid, practical and effective to be used as teaching materials at SMA Negeri 1 O'o'u. Researchers suggest that teachers use this geometry transformation module to improve students problem solving skills